Involvement of Community Organisations in Providing Information, Motivation to TB Patients to Adhere to Regular Treatment - Nixson Manurung; Christina Magdalena T. Bolon; Sarida Surya Manurung; Rostinah Manurung; Sarmaida Siregar; Ratna Dewi; Deddy Sepadha Putra Sagala; Arta Marisi Dame; Syahrul Handoko Nainggolan (Buletin Penelitian Kesehatan, 2025)
Background: Tuberculosis (TB) requires long-term treatment, and non-adherence remains a major challenge that increases the risk of treatment failure and disease transmission. The Information–Motivation–Behavioral (IMB) model highlights the importance of social support in improving adherence. Community-based organizations, particularly youth and religious organizations, are deeply embedded in society and have the potential to support TB patients through information dissemination and motivational assistance. This study aimed to explore the role of community organizations in providing information and motivation to enhance treatment adherence among TB patients. Methods: A qualitative study with a phenomenological approach was conducted in the Serdang Bedagai health service area, North Sumatra, Indonesia. A total of 24 informants, including health workers, members of youth and religious organizations, and TB patients, were recruited using purposive sampling. Data were collected through in-depth interviews and analyzed using qualitative content analysis supported by Atlas.ti software. Results: Three main themes emerged: adherence to treatment, establishment of cooperation, and motivation. Community organizations supported adherence by facilitating regular meetings, assisting medication intake, establishing communication groups, and providing emotional, informational, and family support. Conclusion: The involvement of youth and religious organizations plays a critical role in strengthening TB treatment adherence. Integrating community-based support with health services may enhance motivation, supervision, and long-term treatment compliance among TB patients.